THE FAILURE OF ASEAN COUNTER-TERRORISM COOPERATION IN PREVENTING THE ARRIVAL OF FOREIGN TERRORIST FIGHTERS IN THE MARAWI CONFLICT - Siallagan, Andri (Journal of Terrorism Studies, 2023)
This article examined the elements that contributed to ASEAN counter-terrorism cooperation's failure to prevent the presence of Foreign Terrorist Fighters (FTF) in the Marawi conflict in 2017. The massive ISIS propaganda resulted in an increase in FTF mobilization from several countries to unite the Abu Sayyaf and Maute groups in taking control of Marawi City. This study used a qualitative method and deductive analysis technique by compiling relevant literature on ASEAN's cooperation in counter-terrorism, the FTF problem, and the Marawi conflict. This article would discuss the dynamics of ASEAN cooperation in combating terrorism and the unpreparedness in anticipating the involvement of FTFs in the Marawi conflict. This paper argued that ASEAN counter-terrorism cooperation within the framework of the Convention on Combating Terrorism (ACCT) was ineffective in addressing the presence of FTFs since it did not convert to the practical level and appears to be simply ceremonial. This weakness should encourage ASEAN member nations to reorganize the focus of counter-terrorism cooperation and implement appropriate measures, such as intelligence sharing, border surveillance, prevention of terror financing, and counter-propaganda of terrorists on social media.